Pengaruh Kualitas Layanan dan Persepsi Harga Terhadap Niat Beli Ulang dengan Kepuasan Pelanggan Sebagai Variabel Mediasi - Yadi Supriadi; Endang Tjahjaningsih (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the effect of service quality and price perception on customer satisfaction and its impact on repurchase intention at the Bank Indonesia Tasikmalaya Cooperative. In addition, this study examines the role of customer satisfaction as a mediating variable in the relationship between service quality and price perception toward repurchase intention. This research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to 164 respondents who are members of the Bank Indonesia Tasikmalaya Cooperative. The data were analyzed using multiple linear regression analysis and the Sobel test to examine the mediating effect.The results indicate that service quality and price perception have a positive and significant effect on customer satisfaction. Service quality does not have a significant direct effect on repurchase intention, while price perception has a negative and significant effect on repurchase intention. Furthermore, customer satisfaction has a positive and significant effect on repurchase intention. The Sobel test results confirm that customer satisfaction significantly mediates the effect of service quality and price perception on repurchase intention. These findings imply that improving customer satisfaction is a key factor in encouraging repurchase intention among cooperative members.